Informing the Alfred Registry for Emergency Care Project: An analysis of presenting complaint documentation in an emergency department. (20th April 2022) - White, Matthew; O'Reilly, Gerard M; Mitchell, Rob D; Noonan, Michael; Hiller, Ryan; Mitra, Biswadev; Paton, Andrew; Pristupa, Kathryn; Luckhoff, Carl; Smit, De Villiers; Cameron, Peter A
Abstract: Objective: To assess the feasibility of an ED presenting complaint (PC) tool that categorised all ED PCs into 10 categories. Methods: A retrospective analysis of 1445 consecutive patient encounters was conducted. The primary outcome was the frequency of use of the 10 PC categories. Results: Of the 1203 patient encounters meeting inclusion criteria, the PC tool was completed by clinicians in 574 (47.7%). When completed, the tool's 10 options were selected for most presentations (72.3%). Conclusion: The PC tool captured the majority of presenting complaints in 10 categories. External validation is recommended.